Response of Atmospheric Methane Consumption by Maine Forest Soils to Exogenous Aluminum Salts - Nanba, K. (American Society for Microbiology, 2000)
Atmospheric methane consumption by Maine forest soils was inhibited by additions of environmentally relevant levels of aluminum. Aluminum chloride was more inhibitory than nitrate or sulfate salts, but its effect was comparable to that of a chelated form of aluminum. Inhibition could be explained in part by the lower soil pH values which resulted from aluminum addition. However, significantly greater inhibition by aluminum than by mineral acids at equivalent soil pH values indicated that inhibition also resulted from direct effects of aluminum per se. The extent of inhibition by exogenous aluminum increased with increasing methane concentration for soils incubated in vitro. At methane concentrations of >10 ppm, inhibition could be observed when aluminum chloride was added at concentrations as low as 10 nmol g (fresh weight) of soil(−1). These results suggest that widespread acidification of soils and aluminum mobilization due to acid precipitation may exacerbate inhibition of atmospheric methane consumption due to changes in other parameters and increase the contribution of methane to global warming.